2009
DOI: 10.1111/j.1744-9987.2009.00778.x
|View full text |Cite
|
Sign up to set email alerts
|

Hemoperfusion With an Immobilized Polymyxin B Fiber Column Decreases Macrophage and Monocyte Activity

Abstract: We investigated whether direct hemoperfusion with a polymyxin B column (DHP-PMX) was able to decrease macrophage and monocyte activity in patients with sepsis. Nineteen patients with sepsis were enrolled in the study. They all had signs of systemic inflammatory response syndrome (SIRS) due to infection and a mean arterial blood pressure > or =65 mm Hg (irrespective of the use of catecholamines). A thermodilution catheter was inserted prior to DHP-PMX for intravenous infusion, and DHP-PMX was performed twice wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
2
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 25 publications
2
2
0
1
Order By: Relevance
“…In line with previous studies [ 11 , 30 , 31 ], we found a significant reduction of WBC, specifically neutrophils. During PMX-HP treatment, neutrophils bind with endotoxin, and then the endotoxin–neutrophil complex attaches to polymyxin [ 4 ].…”
Section: Discussionsupporting
confidence: 93%
“…In line with previous studies [ 11 , 30 , 31 ], we found a significant reduction of WBC, specifically neutrophils. During PMX-HP treatment, neutrophils bind with endotoxin, and then the endotoxin–neutrophil complex attaches to polymyxin [ 4 ].…”
Section: Discussionsupporting
confidence: 93%
“…Our results extend the findings of prior studies from our laboratory [19-21] and others [12-16,25,26]. Prior studies found that leukocyte trafficking is highly dependent on cytokine and especially chemokine gradients from the nidus of infection to the circulation [12-16].…”
Section: Discussionsupporting
confidence: 90%
“…Our results indicate that MCP-1 itself or MCP-1-producing cells including monocytes may be absorbed by PMX-DHP. Kushi et al [48] have shown that PMX-DHP decreases macrophage and monocyte activity, and Nishibori et al [49] have used immunocytochemical and microscopic techniques to demonstrate that PMX-DHP binds to monocytes. Although it is unclear whether the reduction of such chemokines has direct or indirect effects, the decreasing MCP-1 levels might partially explain the benefits of PMX-DHP.…”
Section: Discussionmentioning
confidence: 99%